Risk stratification in ST-elevation myocardial infarction is enhanced by combining baseline ST deviation and subsequent ST-segment resolution. Issue 3 (11th October 2007) - Toma, M; Fu, Y; Wagner, G; Goodman, S G; Granger, C; Wallentin, L; Van de Werf, F; Armstrong, P
Abstract : Background: The baseline sum of ST deviation (ΣSTD) and ST segment resolution after fibrinolysis for ST-elevation myocardial infarction are prognostically useful. Objectives: To examine the prognostic impact of ST resolution after fibrinolysis and influence of baseline ST deviation in ASSENT-3. Methods: ST resolution was determined in 4565 patients at 180 minutes after fibrinolysis. 30-Day and 1-year mortality was assessed in patients with complete (ie, ⩾50%) versus incomplete ST resolution according to absolute baseline ΣSTD. Results: Patients with complete ST resolution had lower 30-day and 1-year mortality than those with incomplete ST resolution (3.7% vs 7.3%, p<0.001, and 6.1% vs 10.0%, p<0.001, respectively). After multivariable adjustment for key baseline risk factors, patients with anterior myocardial infarction (MI) in the highest quartile of ΣSTD had a greater risk of 30-day and 1-year mortality than those in the lowest quartile in both complete (odds ratio (OR) = 2.34, 95% CI 1.14 to 4.80, and OR = 2.34, 95% CI 1.26 to 4.34, respectively) and incomplete ST resolution groups (OR = 4.97, 95% CI 1.82 to 13.61, and OR = 3.61, 95% CI 1.55 to 8.4, respectively). However, in patients with inferior MI this pattern only existed when ST resolution was incomplete (OR = 4.88, 95% CI 1.65 to 14.39, and OR = 4.34, 95% CI 1.66 to 11.37, respectively). Conclusion: These findings indicate that percentage ST resolution alone is an incomplete guide to 30-day and 1-year mortality. The integration of both the baseline and post-fibrinolysis ECG provides better risk assessment and can assist in the triage and treatment of such patients.